The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1042/bj2130217
|View full text |Cite
|
Sign up to set email alerts
|

The arsonomethyl group as an analogue of phosphate. An X-ray investigation

Abstract: The X-ray structure analysis of three compounds of interest as enzyme substrates is reported. They are the hydrated forms of (I) DL-2-amino-4-arsonobutanoic acid [HO-AsO2--CH2-CH2-CH(NH3+)-CO2H], (II) DL-2-amino-4-phosphonobutanoic acid [HO-PO2--CH2-CH2-CH(NH3+)-CO2H] and the hydrated barium salt of (III) D-3-phosphoglycerate [HO-PO2--O-CH2-CH(OH)-CO2-]. The structures were fully refined to R factors of 0.033, 0.053 and 0.046. For the compounds (I) and (II) the charge distribution was directly determined by lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…However, 2-arsonoacetyl-L-proline was found to be over 2000-fold weaker an inhibitor than 2-phosphonoacetyl-L-proline. The As-C and As-O bond distances in the former are significantly longer than the P-C and P-O distances in the latter (compare DL-2-amino-4-arsonobutanoic acid and DL-2-amino-4-phosphonobutanoic acid; Kamiya et al, .-1983). These greater bond distances may place an arsenic oxygen atom too far to the left of the active-site zinc atom in angiotensin-converting enzyme (see Fig.…”
Section: Discussionmentioning
confidence: 94%
“…However, 2-arsonoacetyl-L-proline was found to be over 2000-fold weaker an inhibitor than 2-phosphonoacetyl-L-proline. The As-C and As-O bond distances in the former are significantly longer than the P-C and P-O distances in the latter (compare DL-2-amino-4-arsonobutanoic acid and DL-2-amino-4-phosphonobutanoic acid; Kamiya et al, .-1983). These greater bond distances may place an arsenic oxygen atom too far to the left of the active-site zinc atom in angiotensin-converting enzyme (see Fig.…”
Section: Discussionmentioning
confidence: 94%
“…As V shares high chemical similarity to phosphate, as they are both tetrahedral molecules found in group Va of the periodic table and they share three similar dissociation constants. 9,10 The pK a values of arsenic acid (AsO(OH) 3 ) are 2.26, 6.76, and 11.29, and that of phosphoric acid (PO(OH) 3 ) are 2.16, 7.21, and 12.32. 9 Because of the structural similarity between As V and phosphate, As V is a well-known competitive inhibitor of enzymes that involve phosphate, such as glyceraldehyde-3-phosphate dehydrogenase, as well as the sodium pump and anion exchanger in human erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The pK a values of arsenic acid (AsO(OH) 3 ) are 2.26, 6.76, and 11.29, and that of phosphoric acid (PO(OH) 3 ) are 2.16, 7.21, and 12.32. 9 Because of the structural similarity between As V and phosphate, As V is a well-known competitive inhibitor of enzymes that involve phosphate, such as glyceraldehyde-3-phosphate dehydrogenase, as well as the sodium pump and anion exchanger in human erythrocytes. 9,11 As V additionally uncouples oxidative phosphorylation by substituting phosphate in ATP, leading to the formation of ADP-arsenate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these sites is the [3H]AP4 binding site (Butcher et a!., 1983;Monaghan et al, 1983;Bridges et al, 1986), which appears to be the same as the chloride-and calcium-sensitive [ 3H]G1u binding site (Monaghan et at., (Kamiya et al, 1983) shown in two orthogonal views. Note the very similar orientation of all atoms, in particular, the charged amino, carboxyl, and phosphate (L-PSer) or phosphonate (L-AP4) group.…”
Section: Pharmacological Similarity Of L-pser and Lap4mentioning
confidence: 99%